Between the State and the market: defining the non-profit sector in Peru - Portocarrero, Felipe (1998)
This article attempts to define and explain the main characteristics of nonprofit organizations in Peru. The principal factors to take into account in order to understand this Third Sector are the historical weakness of the State and public sectors institutions, as well as their authoritarian and exclusionary nature.   This article first presents the historical framework necessary in order to explain the context, nature and social functions of currently existing nonprofit organizations. Second, the authors examine not only the principal types of formal organizations recognized by Peruvian law, but also the traditional and informal organizations whose activities have acquired a significant presence among the poorest sectors of society. Third, the authors evaluate the extent to which a 'structural-operational' definition of the nonprofit sector, designed for comparative purposes by Lester Salamon and Helmut Anheir of Institute for Policy Studies at Johns Hopkins University, is applicable to the Peruvian case. They conclude with some reflections based on the previous sections.